2022
DOI: 10.3390/ijms23052512
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Analysis of Sphingolipids in Turkeys Fed Fusariotoxins: First Evidence of Key Changes That Could Help Explain Their Relative Resistance to Fumonisin Toxicity

Abstract: The effects of fumonisins on sphingolipids in turkeys are unknown, except for the increased sphinganine to sphingosine ratio (Sa:So) used as a biomarker. Fumonisins fed at 20.2 mg/kg for 14 days were responsible for a 4.4 fold increase in the Sa:So ratio and a decrease of 33% and 36% in C14-C16 ceramides and C14-C16 sphingomyelins, respectively, whereas C18-C26 ceramides and C18-C26 sphingomyelins remained unaffected or were increased. Glucosyl- and lactosyl-ceramides paralleled the concentrations of ceramides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 73 publications
10
4
0
1
Order By: Relevance
“…These results are in agreement with previous ndings in chicken liver and kidney [23,24,27]. The C22-24:C16 ratios, recalculated from data reported in turkey liver [21], were also increased after feeding a diet containing fumonisins. Taken together, these results suggest that the effect of fumonisins on the C22-24:C16 ratios is similar in chickens, ducks, and turkeys.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with previous ndings in chicken liver and kidney [23,24,27]. The C22-24:C16 ratios, recalculated from data reported in turkey liver [21], were also increased after feeding a diet containing fumonisins. Taken together, these results suggest that the effect of fumonisins on the C22-24:C16 ratios is similar in chickens, ducks, and turkeys.…”
Section: Discussionsupporting
confidence: 92%
“…This inhibition led to overexpression of endoplasmic reticulum stress, while CerS2 overexpression protected from FB1-induced damage. Taken together, these results suggest that the increase in the C22-24:C16 ratio observed in chickens and ducks in this study, and previously reported in turkey livers [21], may be an important factor in explaining the interspecies differences in sensitivity to fumonisin toxicity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This occurs in in fowl where the kidney is not the primary target organ. However, urinary Sa/So ratio is still an important biomarker, e.g., in ducks (Tran et al, 2006) and in turkeys (Guerre et al, 2022).…”
Section: Novel Nephrotoxicity Biomarkers Analyzed In Animalsmentioning
confidence: 99%
“…Fumonisin mycotoxins are mainly produced by filamentous fungi Fusarium verticillioides and Fusarium proliferatum and provide at least 28 conformational analogues; these are classified into the sub-groups, A, B, C, and P series (Rheeder et al, 2002). From a toxicological aspect the B series, in particular fumonisin B 1 (FB 1 ) is the most challenging, exerting species-specific and target organ specific effects (Chen et al, 2021;Guerre et al, 2022).…”
Section: Mycotoxin Exposure and General Introduction Of Nephrotoxic M...mentioning
confidence: 99%